Complete Genomic Analysis of VRE From a Cattle Feedlot: Focus on 2 Antibiotic Resistance - Foka, Frank Eric Tatsing; Mienie, Charlotte; Bezuidenhout, Cornelius Carlos; Ateba, Collins Njie (Frontiers in Microbiology, 2020)
Practices in intensive animal farming such as the extensive use of antimicrobials have significant impacts on the genetic make-up of bacterial communities, especially on that of human/animal commensals. In this report, whole genome sequencing of two VRE isolates from a cattle feedlot in the North West Province, South Africa, was used to highlight the threats that extensive antimicrobial usage in intensive animal rearing represents for environmental microbiomes and the food chain. The genomic DNA of the studied strains was extracted using a DNA extraction kit. Whole-genome sequencing was performed through next-generation sequencing. The genomes of E. durans strain NWUTAL1 and E. gallinarum strain S52016 consisted of 3,279,618 bp and 2,374,946 bp respectively with G+C contents of 40.76% and 43.13% respectively. Antibiotic resistance genes, plasmids and virulence factors (involved in biofilm formation, colonisation and copper/silver efflux system), were detected in the genomes of both strains. The presence of these genetic determinants in the studied strains is a cause for concern as they may disseminate and find their way into the food chain via genetic material exchange amongst bacteria of the different ecological niches. Issues of this nature cannot be undermined and are relevant as far as food safety is concerned.